Peran CSR terhadap Keberlangsungan Perusahaan: The Role of CSR in Company Sustainability - Uyun, Linatul; Noviyanti, Sri Eka; Primasari, Dona (JEMeS - Jurnal Ekonomi Manajemen dan Sosial, 2024)
This study aims to explore the role of CSR in corporate sustainability. This study used qualitative research methods, including literature analysis, to identify relevant articles. The criteria for articles in this study are articles published in national and international journals through scholars, Taylor, and Francis. The results show that if companies increase their spending and disclose CSR information in general, then their responsibility towards the environment, employees, and society in particular increases. That is, the impact of corporate CSR disclosure is that it can achieve its goal of maximizing profits in line with sustainable development goals. The results of this study have implications for both managers and practitioners. The results of this study highlight the important question of how increased product innovation, corporate social responsibility (CSR), environmental sustainability, and technological innovation can drive a country's economic growth. Carrying out these activities and maximizing them over a long period of time can build relationships with stakeholders and create a competitive advantage for the company. This study provides an empirical contribution to the impact of CSR on the profitability of companies that implement CSR well.